Load balancing external post-tensioning for strengthening existing inverted-T bent caps. (15th February 2022) - Park, Sun-Hee; Cui, Jilong; Mander, John B.; Terzioglu, Tevfik; Birely, Anna C.; Hurlebaus, Stefan
Highlights: Develop external PT retrofit solution for in-service inverted-T bent caps. Evaluate serviceability of the inverted-T bent caps without and with the PT retrofit. Evaluate accuracy of code-specified ultimate strength predictions in estimating the observed ultimate strength. Design, repair, and retrofit recommendations for in-service inverted-T bent caps are provided. Abstract: Inverted-T bent caps have been widely used to provide increased clearance beneath bridges. Bridges with inverted-T bent caps often experience a prevalence of cracking at the web-to-ledge interface. To prevent these cracks, ledges require sufficient capacity to enable the transfer of applied loads from the girder seats to the pier column. This experimental investigation develops a retrofit solution which uses externally installed post-tensioned strands to balance dead loads thereby improving the capacity of the in-service inverted-T bent caps. Based on experimental results, the solution successfully improved the load carrying capacity of the bents and restrained existing cracks. The cracking load estimation is investigated to evaluate serviceability of the inverted-T bent caps without and with the PT retrofit. Ultimate strength predictions calculated using code-specified sectional methods and limit analysis are compared and contrasted with the experimental observations to evaluate their accuracy in estimating the observed ultimate strength. Based on the experimental observations and analytical comparisons; design, repair, and retrofit recommendations are provided, including their limitations.